EYE PLASTIC SURGERY FOR SEVERE ORBITOPATHY: RESTORING EYE HEALTH AND QUALITY OF LIFE - Silva , Jessica Gabriele Rosa; Bispo, Kamilla Silva; Teixeira, Fernanda Alkmim Rezende; Maciel, Renato Anatolio Lima Horta; Trindade , Luana Magalhães (Brazilian Journal of Implantology and Health Sciences, 2024)
Graves' orbitopathy is a complex and debilitating ophthalmological condition often associated with the autoimmune thyroid disease known as Graves' disease. Characterized by inflammation and swelling of the tissues around the eyes, Graves' orbitopathy can lead to a range of serious symptoms, such as proptosis (bulging eyes), diplopia (double vision), eye pain and impaired visual function. Eye plastic surgery emerges as an important therapeutic approach to restore not only ocular health, but also the quality of life of affected patients, aiming to correct the physical and functional deformities associated with the condition. However, critical evaluation of the scientific literature on the topic is essential to understand the effectiveness, safety and results of the different surgical procedures used in this context. Objective: The objective of this systematic review is to analyze studies published in the last 10 years on ocular plastic surgery for Graves' orbitopathy, with the aim of evaluating the effectiveness, safety and results of the different surgical procedures used to treat this condition. Methodology: Using the PRISMA checklist, articles were searched in the PubMed, Scielo and Web of Science databases, published between 2012 and 2020. The descriptors used were "Graves' Orbitopathy", "Ocular Plastic Surgery", "Thyroid Eye Disease" , "Graves' ophthalmopathy" and "eyelid reconstruction". and "eyelid reconstruction". Inclusion criteria: studies in English, evaluating surgical procedures for Graves' orbitopathy, with clinical and quality of life results. Exclusion criteria: duplicate studies, samples unrelated to Graves' orbitopathy and without relevant clinical results. Results: The main topics covered by the studies include surgical techniques, visual results, postoperative complications and impact on patients' quality of life. Conclusion: The systematic review highlights the importance of ocular plastic surgery in the management of Graves' orbitopathy, providing insights into the most effective and safe surgical approaches to restore ocular health and quality of life to affected patients.